2014
DOI: 10.1210/jc.2013-4280
|View full text |Cite
|
Sign up to set email alerts
|

Macronodular Adrenal Hyperplasia due to Mutations in an Armadillo Repeat Containing 5 (ARMC5) Gene: A Clinical and Genetic Investigation

Abstract: ARMC5 mutations are implicated in clinically severe Cushing's syndrome associated with MAH. Knowledge of a patient's ARMC5 status has important clinical implications for the diagnosis of Cushing's syndrome and genetic counseling of patients and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
98
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 22 publications
17
98
0
6
Order By: Relevance
“…Similarly, pathogenic ARMC5 mutations were found in a second cohort of 34 apparently sporadic cases of BMAH with CS with a prevalence of 20.6% (19) and very recently ARMC5-damaging mutations were identified in 24/98 (26%) index cases of BMAH (20). Furthermore, we and others identified causal germline ARMC5 mutations in six families with BMAH (21,22,23).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similarly, pathogenic ARMC5 mutations were found in a second cohort of 34 apparently sporadic cases of BMAH with CS with a prevalence of 20.6% (19) and very recently ARMC5-damaging mutations were identified in 24/98 (26%) index cases of BMAH (20). Furthermore, we and others identified causal germline ARMC5 mutations in six families with BMAH (21,22,23).…”
Section: Introductionsupporting
confidence: 71%
“…Very recently, Ebelt et al (22) described a German family with a heterozygous c.323_324insC ARMC5 mutation which is the same mutation that we report here, although according to the recommendations by the Human Genome Variation Society, it should be preferentially named c.327_328insC. In contrast to studies on sporadic cases (18,19), we had access to only two BMAH tissues and found a second additional somatic ARMC5 mutation in the BMAH tissue as reported by Gagiardi et al (23). In addition to the causative germline mutation, we found a second germline heterozygous A705V ARMC5 alteration in the daughter who presented a very early onset of severe BMAH (even though a second somatic mutation was not found); although this latest genetic alteration reported as a gene polymorphism (rs11150624) does not affect the main ARMC5 transcript but instead the ARMC5 isoform b precursor, it is intriguing that an isolated non-damaging alteration of a potential ARMC5 transcript accelerates the clinical evolution of the disease.…”
Section: European Journal Of Endocrinologysupporting
confidence: 58%
“…Subsequently, two studies have confirmed that ARMC5 mutations are frequent in PBMAH. ARMC5 mutations were reported in almost 25% of PBMAH index cases in theses series, which include operated as well as non-operated patients (9,40).…”
Section: Armadillo Repeat Containing 5 the Main Genetic Cause Of Pbmahmentioning
confidence: 90%
“…CS in PBMAH is often mild and insidious, even if serious forms can be encountered. PBMAH seems to be predominant in females as observed with other causes of CS (9,10,11). Finally, the exact prevalence of PBMAH in the general population is unknown and dependent of the diagnosis criteria.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation